2022
DOI: 10.3390/ma16010316
|View full text |Cite
|
Sign up to set email alerts
|

Cement Bypass Dust as an Ecological Binder Substitute in Autoclaved Silica–Lime Products

Abstract: The cement industry is one of the most developed industries in the world. However, it consumes excessive amounts of natural resources and can negatively impact the environment through its by-products: carbon dioxide (CO2), cement clinker dust (CKD) and cement bypass dust (CBPD). The amount of dust generated in the cement clinker production process depends largely on the technology used. It typically ranges from 0 to 25% by weight of the clinker, and a single cement plant is capable of producing 1000 tons of CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…The bypass cement kiln dust has two types the first type that produced in the cold section of the furnace while the other type that produced after adding limestone to avoid clogging the ducts. These types have different chemical and physical properties according to the type of raw materials, the technology used for clinker burning, the using fuel and the method used in dust removal [1].…”
Section:  Introductionmentioning
confidence: 99%
“…The bypass cement kiln dust has two types the first type that produced in the cold section of the furnace while the other type that produced after adding limestone to avoid clogging the ducts. These types have different chemical and physical properties according to the type of raw materials, the technology used for clinker burning, the using fuel and the method used in dust removal [1].…”
Section:  Introductionmentioning
confidence: 99%
“…의 재활용을 추진하고 있다 [2][3][4][5] . 염소 바이패스 분진의 주 성분은 칼슘, 알칼리 및 염소 성분으로 구성되어 있으며, 일부 미량의 중금속 성분이 포함되어 있다 6,7) .…”
unclassified
“…Waste materials were also used to produce other building materials, including autoclaved bricks and ballast mixtures. Bork et al [7] used cement bypass dust (CBPD) to produce autoclaved bricks. It has been shown that the amount of CBPD dust used in autoclaved products depends on the chemical composition of the dust and, in particular, on the content of free CaO.…”
mentioning
confidence: 99%